2020
DOI: 10.3390/cells9122642
|View full text |Cite
|
Sign up to set email alerts
|

Common Factors in Neurodegeneration: A Meta-Study Revealing Shared Patterns on a Multi-Omics Scale

Abstract: Neurodegenerative diseases such as Alzheimer’s disease (AD), Parkinson’s disease (PD), Huntington’s disease (HD), and amyotrophic lateral sclerosis (ALS) are heterogeneous, progressive diseases with frequently overlapping symptoms characterized by a loss of neurons. Studies have suggested relations between neurodegenerative diseases for many years (e.g., regarding the aggregation of toxic proteins or triggering endogenous cell death pathways). We gathered publicly available genomic, transcriptomic, and proteom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 294 publications
0
26
0
Order By: Relevance
“…The evidence documented here shows that a deeper understanding of NDs based on multi-omics levels may prompt a shift toward their molecular classification, highlighting both the intrinsic heterogeneity of the pathologies and the differences in involved molecular pathways, as well as the relationships and connections inside the neurodegenerative process itself. Gathering multi omics-layers (genomic, transcriptomic and proteomic data) from 177 studies and more than one million patients suffering AD, PD, Huntington’s disease (HD) and ALS has recently shown a remarkably high number of shared differentially expressed genes between the transcriptomic and proteomic levels for all conditions, shedding light on processes like the humoral immune response, that have previously been described only for certain diseases [ 101 ]. An accurate investigation of complex biological systems by integrating multiple underlying data sources may help to detect shared genetic patterns between the neurodegenerative diseases, identifying biomarkers for differentiating disease states and thereby facilitating the decision-making process and treatment management.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence documented here shows that a deeper understanding of NDs based on multi-omics levels may prompt a shift toward their molecular classification, highlighting both the intrinsic heterogeneity of the pathologies and the differences in involved molecular pathways, as well as the relationships and connections inside the neurodegenerative process itself. Gathering multi omics-layers (genomic, transcriptomic and proteomic data) from 177 studies and more than one million patients suffering AD, PD, Huntington’s disease (HD) and ALS has recently shown a remarkably high number of shared differentially expressed genes between the transcriptomic and proteomic levels for all conditions, shedding light on processes like the humoral immune response, that have previously been described only for certain diseases [ 101 ]. An accurate investigation of complex biological systems by integrating multiple underlying data sources may help to detect shared genetic patterns between the neurodegenerative diseases, identifying biomarkers for differentiating disease states and thereby facilitating the decision-making process and treatment management.…”
Section: Discussionmentioning
confidence: 99%
“…Integrative proteomic and genomic/transcriptomic analyses (in neuroproteogenomics settings) hold great promise for understanding the role of the PTMome in neurodegenerative diseases. For example, a multi-omics data fusion from 177 studies and more than one million patients with AD, PD, HD, and ALS has recently shed light on different biological processes between these pathologies [148]. However, PTMome information was not considered in this integrative study.…”
Section: The Next Step In Neuroproteomicsmentioning
confidence: 99%
“…Protein misfolding is one of the hallmarks in not only HD but also is associated with other neurodegenerative disorders like Alzheimer's Disease (AD), Parkinson's Disease (PD) and amyotrophic lateral sclerosis (ALS). Ruffinni et al (2020) have identified an overlap of 139 genes among HD, AD, PD and ALS, which were also involved in the response to heat and hypoxia (Ruffini et al, 2020). In this context, modulation of heat shock response geneshas also been proposed to be a potential therapeutic target in neurodegenerative diseases associated with misfolded protein aggregates (Ramos et al, 2018;Gomez-Paredes et al, 2021;Labbadia and Morimoto, 2013).…”
Section: Categorymentioning
confidence: 99%